Digitalization of Mathematics Teaching in Hybrid Mode - Galang, Ruby T.; Regala, Angelo D. (Future Science / FSH-PH Publications, 2025)
Global changes have changed our educational system from a pandemic to a new normal. Teachers have adopted new learning delivery to cope with the demands of this era. This change has shifted classroom set-up into online classes, requiring teachers to digitize the education process. With this, different issues of coping mechanisms were explored to make learning possible. This study aimed to explore (1) the perceptions of participants in digitizing math teaching, (2) challenges met in digitalization, and (3) the coping mechanisms to address the issues encountered. It made use of the Narrative research design and employed purposive sampling in choosing its participants. Three semi-structured open ended questionnaire were used in gathering data. Results showed that participants viewed teaching math online as difficult and at the same time engaging. The difficulties faced were seen in students' focus on the discussion, lack of gadgets, computation skills, and digital competency. Various coping mechanism were suggested to cope with the difficulties like; utilizing online application, providing helpful activities and having positive attitudes towards the issue. In conclusion, it is found that teaching math online is difficult as compared to face-to-face classes, hence it is recommended that training on the digital competency and technology must be prioritized to further cope up when teaching math online.